Implementasi Jaringan Informasi, Sarana Bantu serta Kendala yang Dihadapi Perpustakaan - Yusniah Yusniah; Putri Indah Rumpaka; Reni Ayu Pratiwi; Siti Rahmah (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This research was conducted to determine the implementation of the information network. Its implementation is seen from several locations such as IPDN and Bukit Tinggi. Both places are referred to from sources in the form of journals to complement this scientific work. The method that the researcher uses is qualitative research using descriptions and conducting literature studies so as to help the author understand some of the problems by looking at some references. It was found that to implement the information network, it is necessary to make improvements first, such as the procurement of facilities and infrastructure, selecting the right location and several other indicators described in the results and discussion section of the study. Keywords: jaringan, OPAC, perpustakaan.